Peran Pesantren Dalam Penghapusan Kekerasan Terhadap Perempuan - Sugiri, Bunda Sri (UI Scholars Hub, 2007)
Pesantren is one of educational institution which base on religion. Program Interagency Network for Prevention of Violence against Women (VAW) is an innovation to increase the function of Pesantren as a service institution for woman violence victim. The main focus of this program is designing a center of Perlindungan bagi Wanita (Puspita), a women's crises center base on Pesantren. Pesantren set as a center of advocating for woman, because Pesantren has a very strategist task in doing various change in society. However we realized that Pesantren has no distribution yet and also in effort for preventing violation on woman, especially which base on understanding of religion, that has a gender bias.